"I Suck at Everything": Crime, Arrest, and the Generality of Failure. Issue 8 (2nd August 2016) - Pratt, Travis C.; Barnes, J. C.; Cullen, Francis T.; Turanovic, Jillian J.
ABSTRACT: In this article, we advance the idea that getting arrested amounts to "failing at crime." And akin to the notion of the generality of deviance—where those who engage in any given form of criminal behavior are also likely to engage in a wide array of other problematic behaviors—we examine whether failing at crime (getting arrested) is associated with other forms of life failure. Using data from multiple waves of the National Longitudinal Study of Adolescent to Adult Health, our results reveal that, independent of one's level of self-reported criminal behavior and other key potential confounders (IQ and self-control), being arrested is a significant predictor of a host of life failures related to education, employment, relationships, and health. The key implication of our study is that it highlights the need to develop a theory of the "generality of failure."